COMPARISON OF RUSSIAN-SPEAKING SECONDARY SCHOOL STUDENTS’ VALUE CONFLICTS IN THE BALTIC STATES - Mihailova, Sandra; Perepjolkina, Viktorija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
In this research differences between discrepancies in evaluations of value importance and reachability of Russian-speaking high school students from Estonia, Lithuania and Latvia were examined. The study sample included 30 high school students from Latvia, 30 from Estonia and 30 from Lithuania aged 16 to 18. All students completed value-rating survey developed by Fantalova (Fantalova, 2011) and demographic questionnaire. Results have shown that the key values in all the Baltic countries are similar: health, love, happy family and friends. There is basically no statistically significant difference between value importance, value reachability, and value conflicts. Statically significant differences between Latvian and Lithuanian pupils are in the following values: beauty of nature and art, but there are statistically significant differences between Latvian and Estonian pupils in the following values: materially secured life, interesting work. It was found that in these three samples value conflicts don’t creates enough tension to motivate action. It can thus be assumed that the migration of school graduates possibly is not linked to the inability to realize the values that are important to them in their country. As the tension between values grows, the reasons why young people emigrate from one of the Baltic countries may be different.